2001
DOI: 10.1088/0022-3727/34/19/303
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence microscopy of hydrothermal and flux grown ZnO single crystals

Abstract: Bulk ZnO single crystals grown by the hydrothermal and flux methods have been characterized by steady-state and time resolved cathodoluminescence measurements performed on the different crystalline faces. A shift of the peak near band edge towards lower energies is observed in spectra recorded with increasing delay times. This behaviour is often observed in the etch pit regions in alkali flux grown crystals, which suggests the presence of a band related to dislocations or to the point defects surrounding the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Meyer et al 13 concluded that a sharp line of excitonic character at around 3.333 eV found in bulk ZnO shows most of the established features of Y recombination line commonly seen in ZnSe and ZnTe ͑exciton bound to dislocations and other extended structural defects͒. Urbieta et al 24 observed in bulk ZnO samples an emission at 3.1 eV by cathodoluminescence and they concluded that it was related to dislocations.…”
Section: Resultsmentioning
confidence: 99%
“…Meyer et al 13 concluded that a sharp line of excitonic character at around 3.333 eV found in bulk ZnO shows most of the established features of Y recombination line commonly seen in ZnSe and ZnTe ͑exciton bound to dislocations and other extended structural defects͒. Urbieta et al 24 observed in bulk ZnO samples an emission at 3.1 eV by cathodoluminescence and they concluded that it was related to dislocations.…”
Section: Resultsmentioning
confidence: 99%
“…Decoration of dislocations with defects influences optical and luminescent characteristics of near-dislocations regions [16,17]. In particular, accumulation of shallow donors at dislocations was proved to result in the shift of optical absorption edge to the long wavelength side and distortion of edge luminescence spectrum in CdS [19].…”
Section: Experimental and Discussionmentioning
confidence: 99%
“…To record CL spectra at different delay times, the signal from a photomultiplier was collected by a boxcar integrator ͑PAR162͒ triggered by the pulse generator, and then fed to a computer ͑see Ref. 20 for further details͒. The time resolution of the TRCL setup is about 100 ns, while the spectral resolution is 2 nm.…”
Section: Methodsmentioning
confidence: 99%